2019
DOI: 10.1101/758532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parietal Cortex Integrates Object Orientation and Saccade Signals to Update Grasp Plans

Abstract: AbstractCoordinated reach-to-grasp movements are often accompanied by rapid eye movements (saccades) that displace the desired object image relative to the retina. Parietal cortex compensates for this by updating reach goals relative to current gaze direction, but its role in the integration of oculomotor and visual orientation signals for updating grasp plans is unknown. Based on a recent perceptual experiment, we hypothesized that inferior parietal … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
72
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(90 citation statements)
references
References 63 publications
17
72
1
Order By: Relevance
“…Figure 4a provides a general overview of the data used in this calculation, showing Saccade > Fixation modulations during the updating portion of our task and for reference, the same contrast from our saccade localizer task, where participants simply looked back and forth between two points (see Methods for details). As in our previous study [24], saccade modulations were generally more widespread when they accompanied a more complex task. Figure 4b shows that the location of the vPCu site used for our hypothesis testing bordered on the edge of a major cluster of saccade modulation.…”
Section: Hypothesis 2: Task-specific Saccade Modulationssupporting
confidence: 83%
See 4 more Smart Citations
“…Figure 4a provides a general overview of the data used in this calculation, showing Saccade > Fixation modulations during the updating portion of our task and for reference, the same contrast from our saccade localizer task, where participants simply looked back and forth between two points (see Methods for details). As in our previous study [24], saccade modulations were generally more widespread when they accompanied a more complex task. Figure 4b shows that the location of the vPCu site used for our hypothesis testing bordered on the edge of a major cluster of saccade modulation.…”
Section: Hypothesis 2: Task-specific Saccade Modulationssupporting
confidence: 83%
“…Our previous study of transsaccadic orientation updating showed a functional network connecting right SMG to both saccade and grasp motor areas [24]. Here, we provide a similar analysis of precuneus activity for the current perceptual task.…”
Section: Hypothesis 2: Task-specific Saccade Modulationssupporting
confidence: 58%
See 3 more Smart Citations